Multistage stochastic programs with a random number of stages: dynamic programming equations, solution methods, and application to portfolio selection. (2nd January 2021) - Guigues, Vincent
Abstract : We introduce the class of multistage stochastic optimization problems with a random number of stages. For such problems, we show how to write dynamic programming equations and how to solve these equations using the Stochastic Dual Dynamic Programming algorithm. Finally, we consider a portfolio selection problem over an optimization period of random duration. For several instances of this problem, we show the gain obtained using a policy that takes the randomness of the number of stages into account over a policy built taking a fixed number of stages (namely the maximal possible number of stages).